2020
DOI: 10.1186/s12884-020-2721-9
|View full text |Cite
|
Sign up to set email alerts
|

A condom uterine balloon device among referral facilities in Dar Es Salaam: an assessment of perceptions, barriers and facilitators one year after implementation

Abstract: Background: Postpartum hemorrhage (PPH) is the leading cause of maternal death in Tanzania. The Every Second Matters for Mothers and Babies-Uterine Balloon Tamponade (ESM-UBT) device was developed to address this problem in women with atonic uterus. The objective of this study was to understand the barriers and facilitators to optimal use of the device, in Dar es Salaam Tanzania 1 year after implementation. Methods: Semi-structured interviews of skilled-birth attendants were conducted between May and July 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Qualitative studies of ESM‐UBT use among providers in Tanzania, Kenya, Senegal, and Sierra Leone demonstrated that the device was widely accepted, easy to use, and helpful in managing refractory PPH and averting emergency hysterectomy. 17 , 18 , 19 , 20 Our findings are consistent with previous studies and support implementation of the ESM‐UBT package in tertiary referral centers and their networks. Our study contributes several key points to consider with future ESM‐UBT implementation in low‐resource settings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Qualitative studies of ESM‐UBT use among providers in Tanzania, Kenya, Senegal, and Sierra Leone demonstrated that the device was widely accepted, easy to use, and helpful in managing refractory PPH and averting emergency hysterectomy. 17 , 18 , 19 , 20 Our findings are consistent with previous studies and support implementation of the ESM‐UBT package in tertiary referral centers and their networks. Our study contributes several key points to consider with future ESM‐UBT implementation in low‐resource settings.…”
Section: Discussionsupporting
confidence: 91%
“…This study contributes to a larger body of evidence supporting UBT use in a variety of settings. Qualitative studies of ESM‐UBT use among providers in Tanzania, Kenya, Senegal, and Sierra Leone demonstrated that the device was widely accepted, easy to use, and helpful in managing refractory PPH and averting emergency hysterectomy 17–20 . Our findings are consistent with previous studies and support implementation of the ESM‐UBT package in tertiary referral centers and their networks.…”
Section: Discussionsupporting
confidence: 89%
“…Future studies should explore additional strategies to improve both implementation and service outcomes for the UBT. For example, improvements in training rates, fidelity to learnt methods and sustained use may be achieved with pre-service and in-service curriculums incorporating UBT devices, facility-based mentorship programmes supporting individual UBT-use, group refresher trainings (especially at low-volume facilities or where staff turnover is high), high-fidelity team practice simulations prior to emergency situations, advocacy for UBT use by local champions and Ministry of Health supervisor visits to monitor use and storage 7 36–39. Both Ghana and Kenya have illustrated a strong commitment to equip health providers with the proper tools to strengthen skills via training and supportive mentorship.…”
Section: Discussionmentioning
confidence: 99%
“…Daniel Surbek have analyzed, and conclusions were made by the Swiss PBM in obstetrics working group of experts in a consensus meeting [29]. Oluwakemi Adegoke developed the Every Second Matters for Mothers and Babies by using Uterine Balloon Tamponade (ESM-UBT) device which is used to control the blood to the uterus [30,31]. Marieke C. Punt [29] has revealed obstetric bleeding problems often occur in women with Inherited Platelet Receptor Defects (IPRD).…”
Section: Literature Reviewmentioning
confidence: 99%